The Degree in Which Quality of Life Contributes to Predicting the Level of Depression Among Mothers of Children with Chronic Kidney Disease in the Governorate of Amman - Alkhatatneh, Sami Mohsen (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aimed to identify the level of quality of life and its relationship to depression among mothers of patients with kidney failure in Jordan and the extent to which quality of life contributes to depression. Methodology: The study sample consisted of (348) mothers of patients with kidney failure in the Amman Governorate. To achieve the study’s objective, a quality of life scale and a depression scale were developed. After referring to theoretical literature and previous studies, the validity and reliability of the study tools were verified. Results: The results of the study showed that there was a low level of quality of life and a moderate level of depression among mothers of patients with kidney failure in the Amman Governorate. The results also indicated that there was a statistically significant inverse correlation at the level (α = 0.01) between the level of quality of life and the level of depression. The results revealed that quality of life explained 12% of the variance in the level of depression. Conclusions: The study recommended that the Ministry of Health adopt, in its policy and objectives, measures that support the quality of life and adress the causes of depression among patients and their families, especially those with kidney failure. It also suggests activating the role of psychological and social counseling departments in hospitals by educating patients’ families, particularly those with kidney failure, about the importance of quality of life, which plays a crucial role in reducing their level of depression.